(untitled) (Journal of Industrial and Mechanical Engineering, 2024)
This work shows the development of a three-bladed propeller, based on a fluid agitator with an Axial type design; used for low viscosity fluids (<8 Pa.s / <8000 cP) and to homogenize, with N.A.S.A. (ex-N.A.C.A) profiles. with a tangential speed of between 3m/s and 15 m/s. The propeller prototype made using 3D printing techniques is presented. Likewise, it was tested in a simulation and real test using 3 different speeds. It could be observed how the speed at the leading edge is the same as the trailing edge, which guarantees that the design of the hydrodynamic profile is correct. Accompanying this observation, the zero presence of cavitation in the propeller is detected at the three requested speeds.